Eksplorasi Efektivitas Pengembangan Media Pop-Up Book Bertema Siklus Hidup Kupu-Kupu dalam Meningkatkan Pemahaman Siswa Kelas IV Madrasah Ibtidaiyah - Ainun Izza Afkarina; Muhammad Suwignyo Prayogo; Bella Rizki Prahadiyanti (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to measure the effectiveness of Pop-Up Books with the theme “The Life Cycle of Butterflies” in improving the understanding of fourth-grade students at Madrasah Ibtidaiyah (MI). This media is designed as an attractive and interactive learning tool that is relevant to everyday life, helping students understand the concept of the life cycle of living things, especially butterflies. The approach used in this study is descriptive qualitative, with data collection through observation, interviews, and documentation. The research subjects included fourth-grade MI students. The data were analyzed in three stages: data reduction, data presentation, and conclusion drawing. The results showed that the use of Pop-Up Books successfully attracted students' interest and attention, increased their motivation to learn, and facilitated their understanding of the stages of the butterfly life cycle. Teachers also provided positive feedback on this media because it supported an active, creative, and enjoyable learning process. Thus, it can be concluded that the Pop-Up Book media with the theme “Butterfly Life Cycle” is effective in science learning to improve the conceptual understanding of fourth-grade Madrasah Ibtidaiyah students.